METHODS OF QUANTITATIVE LINGUISTICS IN THE STUDY OF THE WRITER’S IDIOSTYLE (BASED ON LYUKO DASHVAR’S WORKS) - Shytyk, Liudmyla; Shcherbyna, Tetyana (Linguistic Bulletin (Movoznavchyi Visnyk), 2024)
Introduction. In the era of information technology development, linguistic phenomena require not only qualitative but also quantitative study. Considering this, interdisciplinary studies focused on applying statistical methods to the analysis of linguistic objects have become particularly relevant. Quantitative characteristics of the lexical content of a text are one of the important components of a comprehensive analysis of literary speech and the author’s individual style characteristics. Purpose. The purpose of the article is to study the specifics of Luko Dashvar’s idiolect by modelling the statistical profile of the writer’s texts, as well as to analyse the quantitative indicators of the methods of introducing traditional and transformed phraseological units into works of fiction as a distinctive sign of the author’s individual speech. Methods. Statistical methods were used to analyse the quantitative correlation of the varieties of the studied phraseological units; methods of quantitative and computational linguistics were used to clarify the applied aspects of the study of the methods of introducing phraseological units. Results. The use of corpus technologies and quantitative linguistics methods made it possible to study the statistical profile of Luko Dashvar’s works and to demonstrate the uniformity of the representation of quantitative data in each of the analysed novels. The significance of the statistical difference between the coefficient values was determined using the χ2 calculation; the degree of freedom of the transformed phraseological units was defined on the material of the novel «The Smell of Meat». The analysed samples were found to be statistically homogeneous, and the study of the degree of freedom proved that the differences in the quantitative composition between the compared samples are not significant. The diversity coefficient for transformed phrasemes in the novel «Rai.Tsentr» and the Spearman’s rank correlation coefficient are determined on the basis of three novels «Milk with Blood», «The Smell of Meat» and «Rai.Tsentr». The lexical diversity of the texts is proved on the basis of the determined coefficients. Originality. For the first time, quantitative parameterization of Luko Dashvar’s texts was performed, and the statistical characteristics of the transformed phrasemes of the writer’s novels were represented. Conclusion. Quantitative methods provide accurate, structured data on the features of the author’s style, linguistic richness of the text and the functional load of language units. They serve as an effective tool for researching Luko Dashvar’s works, as they allow for a deeper analysis of her linguistic strategies, stylistic preferences, and uniqueness in the context of contemporary fiction writing.